LAJU PEMBUANGAN PANAS PADA RADIATOR DENGAN FLUIDA CAMPURAN 70% AIR DAN 30% RADIATOR COOLANT DENGAN RPM 2000 TOYOTA AVANZA - Heri Wijanarko; Sugihandoko; Suparyana (PPM Sdirjianbang Akademi Militer, 2022)
Cars that are used to travel long distances are usually driven at a fairly high speed with engine speed ranging from 2000 rpm and in a fairly long period of time. In order not to happen things that are not desirable due to the engine temperature exceeds the normal temperature of the machine when working, then this study needs to be done. In this study conducted comparative testing of engine heat dissipation rate between the use of 100% water with a mixture of 70% water and 30% radiator coolant with paired comparison method at rpm 2000. From the research, data were taken, among others, the temperature of the radiator Inlet and outlet, and the volume of radiator fluid flow (Q) which is then processed data to determine the mass flow rate (m), the specific heat of the fluid (Cp), the rate of heat dissipation radiator (q), and statistical data processing. The results of testing of a mixture of 70% water radiator fluid and 30% radiator coolant showed an average difference between the inlet temperature of the radiator with a higher radiator outlet temperature of 4.7250 C and the average heat dissipation rate of the radiator is also higher at 8.02931 kJ/s. This condition shows that at 2000 rpm, a mixture of 70% water and 30% radiator coolant has a higher engine heat absorption and dissipation capability than 100% water.